2021
DOI: 10.15446/profile.v23n1.85019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Assessment Training on EFL Writing Classroom Assessment: Voices of Mexican University Teachers

Abstract: The extent to which writing assessment training (WAT) impacts writing scores has been widely explored in L2 testing contexts. However, little is known of the benefits of WAT to classroom assessment of writing. This paper analyzes the impact of two WAT sessions on the classroom assessment of writing of eleven EFL Mexican university teachers. Twenty-two interview transcripts suggested an impact in three main areas: classroom teaching of writing, classroom assessment of writing, and teacher self-awareness. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
0
3
0
2
Order By: Relevance
“…The large percentage of instructors stated that written feedback was one of the most promising strategies to educate learners to write. Individuals might strengthen their writing skills with the assistance of specialized instruction and expert written guidance (Hamp-Lyons & Jin, 2022;González, 2021). Thus, facilitating learners to create legible writings seems to be a primary consideration for these lecturers (Lu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large percentage of instructors stated that written feedback was one of the most promising strategies to educate learners to write. Individuals might strengthen their writing skills with the assistance of specialized instruction and expert written guidance (Hamp-Lyons & Jin, 2022;González, 2021). Thus, facilitating learners to create legible writings seems to be a primary consideration for these lecturers (Lu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…What are the ultimate goals of a writing course beyond strengthening grammar? The lack of emphasis on substance, inventiveness, and coherence also implies that in-depth research on the requirement for expert feedback coaching should be promoted prior to teaching any EFL writing classes (González, 2021;Almahasneh & Abdul-Hamid, 2019;Ahmed & Abouabdelkader, 2016). This may then lead to the identification of which instructor comments assist student writers in significantly enhancing the global aspects of their works, and which comments actually help writers with the acquisition of skills and approaches that can be transferred from one writing task to another.…”
Section: Positive Feedbacks On Global Issues (Macro-level)mentioning
confidence: 99%
“…The main point here is the fact that very few rural primary teachers have not been involved in the professional development strategies launched by MEN because these programs have been focused specifically on English language teachers. Studies conducted by Cárdenas and Chaves (2013), Cadavid et al (2004), and González and Montoya (2010) demonstrated that the most part of primary teachers could not have access to MEN's initiatives because they do not have English language teaching degrees. However, rural schools have a huge potential and opportunities to foster not only the English language but also other skills such as language development, learning and teaching, evaluation procedures, research and technology incorporation, leadership, and problem solving.…”
Section: Professional Developmentmentioning
confidence: 99%
“…Por un lado, la evaluación de habilidades receptivas implica tareas de desempeño, abiertas o cerradas, centradas en la lectura o en la audición de textos (Katz, 2014). Por otro lado, la evaluación de habilidades productivas incluye tareas abiertas que involucran la oralidad o la escritura, complementadas con instrumentos como escalas de apreciación o rúbricas con criterios e indicadores de desempeño (González, 2021).…”
Section: Evaluación En El Proceso De Enseñanza-aprendizaje Del Inglésunclassified